(untitled) (Journal of Pharmaceutical Negative Results, 2022)
An o/w nanoemulsion (NE) was used with an objective to select appropriate components including emulsifiers (surfactants and cosurfactants) and oils as well as the NE area of emulsifier ratio (Smix). Aqueous titration method was used to construct triangular co-ordinate emulsion diagrams. Tween 80 and cremephore EL as surfactant and ethanol as co-surfactant were used as emulsifiers with ratio 1:1 and 1:2 , oleic acid was used as oily phase. Twelve nanoemulsion formula was prepared by using aqueous titration method (low energy emulsification).The NE was characterized for visual transparency, average droplet size, polydispersity index, zeta potential, % transmittance, drug content and in-vitro drug release.The formula F11 were selected as optimum nanoemulsion according to results of characterization. (F11) nanoemulsion with Smix (1:2) : oil : deionized water (55: 5: 40) ratio is the optimized formula (best formula), because it is characterized by good droplet size range (16.9 nm), good PDI (0.552), good percent transmittance (99. 4%), percent of drug content was higher (98.5) and highest release of tizanidine from the formula.